A Comprehensive Research on Antibiotic Resistance Genes in Microbiota of Aquatic Animals - Hong, Bin; Ba, Yongbing; Niu, Li; Lou, Fei; Zhang, Zhaohuan; Liu, Haiquan; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2018)
Antibiotic resistance genes (ARGs) are emerging contaminants posing potential risks to human health. Antibiotics used in aquaculture have promoted the evolution and spread of ARGs in aquaculture environment. This study aimed to investigate the occurrence of 37 ARGs conferring resistance to six classes of antibiotics in 94 aquatic animals from five cities in southeast coast of China. The results showed that floR, sulII, sulI, strB, strA, aadA, and tetS were identified as the prominent ARGs with the high detection frequencies ranging from 30.9% to 51.1%. The relative expression amount of seven prominent ARGs mentioned above ranged from 0.003 to 0.065, quantified by quantitative real-time PCR (qPCR). The tetS was also the most abundant ARG among the seven ARGs. Though aadA was the second highest detection frequency of ARGs, it was the lowest expression amount ARG. The occurrences and abundances of ARGs in freshwater animals were greater than those in marine aquatic animals. Shanghai was considered as the most prevalent site with 16 ARGs, and Ningbo merely contained 9 ARGs with none of β-lactam ARGs and quinolone ARGs, showing variations of ARGs with geographical location. Eight kinds of sulfonamides and one chloramphenicol residues were further measured in samples from Shanghai. Interestingly, no target antibiotics were found, but sulfonamides resistance genes (sulI, sulII) and chloramphenicol resistance genes (floR) persisted at aquatic animals in the absence of selection pressure. Our research reveals that aquatic animals have become a potential vehicle to aggregate and spread ARGs, and it is a reference for potential risks to human health.